Sistem Pendukung Keputusan Pemilihan Security Officer Pada PT Kharisma Esa Unggul Menggunakan Metode VIKOR - William Dhaniel Tampubolon (CV. Graha Mitra Edukasi, 2025)
A security officer is a security unit or security group established by a business entity to ensure physical security in the environment where they are assigned. The duties of a security officer include maintaining safety and order in their work area and surroundings, covering physical security. Security officers also act as sources of information, protect, and serve the public and surrounding environment. A security officer is a unit or group of personnel formed by an institution or business entity to carry out physical security as part of organized self-managed security within the work environment. The issue that arises in selecting security officers at PT Kharisma Esa Unggul is that the company conducts basic evaluations, primarily assessing skills and applying subjective judgment, meaning the company relies on relative impressions, assumptions, feelings, or preferences. A Decision Support System (DSS) is a system that plays a role in supporting the decision-making process in an organization or company. Therefore, for selecting security officers, each alternative must have criteria, and each criterion should have a predetermined weight, followed by a resolution process using the Vise Kriterijumska Optimizacija I Kompromisno Resenje (VIKOR) method for ranking. In this study, the result of the VIKOR method calculation showed that Aziz Marbun (A2) achieved the highest score of 0. The calculated ranking score for selecting a security officer ranges from 0 to 1. This approach helps the company make security officer selections in an accurate, efficient, and precise manner.